Comparison of the effects of the ligation of ascending branches of bilateral arteria uterina with tourniquet method on the intra-operative and post-operative hemorrhage in abdominal myomectomy cases - Sapmaz, E; Çelik, H (Elsevier Sci Ireland Ltd, 2003)
Objective: To compare the effects of ligation of the ascending branches of the uterine artery and tourniquet methods intra-operative and post-operative hemorrhage during. abdominal myomectomy. Methods: Fifty-one cases with symptomatic myoma uteri were prospectively, randomly assigned to two single blind groups. Myomectomy was performed in Group I (n = 26) by bilateral ligation of the ascending branches of the uterine artery and in Group 2 (n 25) by the intra-operative tourniquet method. Mann-Whitney U, Wilcoxon Rank and chi(2) tests were used in the comparison of the data. Spearman correlation analysis was used to determine the correlation between myoma enucleation, operation duration and blood loss (r(s), P, n). Results: Operation time, number of removed myoma nuclei, (P > 0.05, Mann-Whitney U test), and febrile morbidity were similar in the two groups (P > 0.05, chi(2) test). Intra-operative blood loss was lower in Group I (P < 0.05, Mann-Whitney U test). In three cases from Group 2 post-operative hemorrhage occurred, and the laparotomy and bilateral ligation of the internal iliac arteries were performed in these cases. There was a positive correlation among myoma enucleation, operation duration and blood loss (r(s) = 0.7, P = 0.001, n = 5 1). Conclusions: Intra-operative blood loss is lower with bilateral ligation of the ascending branches of the uterine artery during myomectomy. The effect of ligation on hemorrhage continues in the post-operative period. (C) 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: abdominal myomectomy; the ligation of bilateral arteria uterina; hemorrhage; tourniquet